What if they had not Gone Negative? A Counterfactual Assessment of the Impact from Negative Interest Rates - Michail, Nektarios A. (My University, 2019)
The counterfactual estimation technique of Pesaran and Smith () is employed to provide an assessment of the impact stemming from the implementation of negative interest rates in three European economies (Denmark, Sweden and Switzerland). The analysis indicates that negative interest rates did not have a significant effect on bank lending growth or inflation in any country. This failure to reject the policy ineffectiveness hypothesis most likely lies in the fact that negative interest rates did not ease the situation for the factors restricting the supply of bank lending, namely bank funding costs and Return-on-Equity.
Keywords: Estimation technique; Negative interest rates; European economies